2014
DOI: 10.1021/es500916v
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Prions in Compost

Abstract: Composting may serve as a practical and economical means of disposing of specified risk materials (SRM) or animal mortalities potentially infected with prion diseases (transmissible spongiform encephalopathies, TSE). Our study investigated the degradation of prions associated with scrapie (PrP(263K)), chronic waste disease (PrP(CWD)), and bovine spongiform encephalopathy (PrP(BSE)) in lab-scale composters and PrP(263K) in field-scale compost piles. Western blotting (WB) indicated that PrP(263K), PrP(CWD), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 57 publications
2
32
0
2
Order By: Relevance
“…The SSC opinion (2001) considered that mechanical contamination of plant leaves by prions was theoretically possible following the spreading of organic fertilisers, manure, blood, incinerator ash, sewage sludge or rendering condensate. Recent work (Xu et al, 2014) suggests that the composting of waste materials results in a reduction in detectable PrP Sc (BSE) of one log within 28 days, but Pritzkow et al (2015) have demonstrated that topically applied infectious material resulted in retention of PrP Sc for several weeks in the living plant. They have also demonstrated that plants can take up prions from contaminated soil and transport them to aerial parts of the plant (stem and leaves), thereby efficiently binding prions and acting as potential carriers of infectivity.…”
Section: Environmental Contaminationmentioning
confidence: 99%
“…The SSC opinion (2001) considered that mechanical contamination of plant leaves by prions was theoretically possible following the spreading of organic fertilisers, manure, blood, incinerator ash, sewage sludge or rendering condensate. Recent work (Xu et al, 2014) suggests that the composting of waste materials results in a reduction in detectable PrP Sc (BSE) of one log within 28 days, but Pritzkow et al (2015) have demonstrated that topically applied infectious material resulted in retention of PrP Sc for several weeks in the living plant. They have also demonstrated that plants can take up prions from contaminated soil and transport them to aerial parts of the plant (stem and leaves), thereby efficiently binding prions and acting as potential carriers of infectivity.…”
Section: Environmental Contaminationmentioning
confidence: 99%
“…A number of studies have demonstrated biodegradation of prion protein using compost (Huang et al 2007;Xu et al 2013). In a field trial, Xu et al (2014) also observed that composting reduced PrP TSE , resulting in one 50% infectious dose (ID50) remaining in every 5,600 kg of final compost for land application.…”
Section: Coll Et Al (2007) Measured the Effectiveness Of VersazymeÂź mentioning
confidence: 99%
“…have also been demonstrated by researchers. [2,[21][22][23] Still, there is a massive demand for a low cost material based efficient technique which can rapidly oxidize relatively lower concentration of the aqueous As(III) and removes arsenic from the water subsequently.…”
Section: Introductionmentioning
confidence: 99%